Electrical and optical properties of a nanocomposite based on polyvinyl alcohol and fullerenol - Nikitina Elizaveta; Kapralova Viktoria; Sudar Nicolay; Studzinskii Vitalii; Gerasimov Victor (St. Petersburg Polytechnical University Journal: Physics and Mathematics)
This work presents the results of comparison of optical properties at room temperature and electrical characteristics of films of polyvinyl alcohol (PVA) and nanocomposite based on PVA with small additives of fullerenol C60(OH)44 in a wide frequency range (25 Hz – 1 MHz) at temperatures from 294 to 398 K. The addition of 2 wt.% fullerenol leads to a significant absorption of light by such a film in the UV region of the spectrum (IR spectra of both film samples were identical), as well as to a decrease in dielectric permittivity ε'. The ε'' frequency dependences of both films showed peaks in the low-frequency region, which shifted towards higher frequencies when the films were heated. The values of the activation energy of conduction at direct current for PVA and polymer nanocomposite were found to be about 1.5 eV. An explanation of the observed effects is proposed.